Spring in action - Walls, Craig (Manning Publications Co., 2022)
Spring in Action, Sixth Edition is a comprehensive guide to Spring’s core features, all explained in Craig Walls’ famously clear style. You’ll put Spring into action as you build a complete database-backed web app step-by-step. This new edition covers both Spring fundamentals and new features such as reactive flows, Kubernetes integration, and RSocket. Whether you’re new to Spring or leveling up to Spring 5.3, make this classic bestseller your bible!